ULUMUL QUR’AN UNTUK MASA KINI - MUHAMMAD BAHRUDIN (STIT DARUL ULUM KOTABARU, 2023)
Scholars and Al-Quran scholars place Ulumul Quran in the main position of many Islamic studies. Ulumul Quran are sciences that are closely related to the Arabic Al-Quran and are useful for obtaining interpretations that can be justified. With a qualitative method, we can see how the scholars tried their best to produce the writings of 'Ulumul Quran to make it easier for researchers to understand and interpret the Quran. From the results of this research, especially for the current generation, it is hoped that it will be useful in dealing with differences in understanding that are still not contradictory to the Al-Quran with high tolerance and also open the eyes of the current generation that there are many sciences that can be learned in 'ulumul quran as a reference for science and technology for life to be stable and balanced.